Intravenous thrombolysis and risk of early-onset post-stroke depression: a propensity score matched cohort study - Lu, Jieyi; Zhang, Lulu; Zhang, Yi; Mao, Huawu; Fang, Qi (Frontiers in Neurology, 2024)
Background Depression is common in stroke survivors and affects their recovery and quality of life (QoL). Intravenous thrombolysis (IVT) can improve post-stroke outcomes but the impact on early-onset post-stroke depression (PSD) is unclear. This was evaluated by comparing depression symptoms between patients with acute ischemic stroke (AIS) with vs. without IVT. Methods This retrospective cohort study included 633 patients with AIS. The 17-item Hamilton Depression Rating Scale was used to evaluate depression in patients 14–21 days after stroke onset. Propensity score matching was used to minimize intervention bias between the two groups. Results Of the 633 patients, 120 (19.0%) received IVT and 513 (81%) did not. Before matching, the prevalence of early-onset PSD was lower in the IVT group than in the non-IVT group (18.3% vs. 29.2%, p < 0.05). In the multivariate logistic regression analysis, the risk of early-onset PSD was significantly lower in the IVT group than in the non-IVT group [odds ratio (OR) = 0.48; 95% confidence interval: 0.28–0.83]. The results were stable after adjusting for potential confounders by inverse probability of treatment weighting and using a pairwise algorithm based on propensity scores (ORs between 0.44 and 0.61, all p < 0.05); were robust to unmeasured confounding as assessed by E-value analysis; and were consistent in subgroup analyses. Conclusion IVT is associated with a reduced risk of early-onset PSD and can improve the QoL of patients with AIS during post-stroke recovery.